The analysis of food symbols in the ‘Serarang’ ritual of the Melanau Likow community in Dalat, Sarawak - Noor Norazila Inai; Mohamad Maulana Magiman; Norhuda Salleh; Ahmad Nasir Mohd Yusoff; Mangai Tugau; Septian Aji Permana (Primrose Hall Publishing Group, 2020)
The Serarang ritual is a form of performance performed in the Melanau Likow community to be presented to Ipok. The presentation consists of symbolic elements based on each type of food served. These symbolic elements are involved with the belief and cosmological system that surround the lives of Melanau Likow. The main focus of this research is to analyse the symbol of food in the Serarang ritual from the viewpoint of non-verbal communication. This research used an ethnographic approach and the researchers also participated in the ritual. The data was collected through an in-depth interview with the main informant, Tama Kaul, and with the other ritual practitioners. The research was conducted in Kampung Medong, Dalat Sarawak. The data analysis found that the food that was delivered to Ipok had its own meaning and could be interpreted through shape, colour, and the way it was presented. The food in the Serarang tray means love, gratitude, prayer, and hope for more sustenance in the upcoming year. The research also found that the ritual is still practiced to this day by the Melanau Likow community and becomes the identity of its existence in the state of Sarawak.